The Importance of Sport Games in Creating a Healthy Environment in the Family: Pentingnya Olahraga Permainan dalam Menciptakan Lingkungan Sehat dalam Keluarga - Rashidov Khurshid Karimovich; Urinov Sherali Raufovich (Academia Open, 2022)
This study presents a comprehensive analysis of the pivotal role and significance of physical education in reducing family budget expenditures. The primary objectives were to identify important tasks within physical education and assess their impact on family finances. Using a sample of 100 families, a mixed-methods approach was employed to collect and analyze data. The results highlight the crucial need to prioritize physical education, with substantial findings demonstrating its positive influence on reducing family expenses. The implications of this research emphasize the potential for physical education to alleviate financial burdens and suggest a reevaluation of resource allocation in households worldwide. This study provides a compelling argument for policymakers, educators, and researchers to recognize and prioritize physical education as an effective strategy for managing family budgets. Highlights: Physical education's role in reducing family budget: This article analyzes the crucial role of physical education in reducing family budget expenditures and highlights its significance as a cost-saving measure. Findings from 100 family cases: The study draws upon a sample of 100 families to substantiate the importance of physical education in managing family budgets, providing empirical evidence for its impact. Implications for policy and practice: The research underscores the need to prioritize physical education, offering implications for policymakers, educators, and researchers to recognize its potential in alleviating financial burdens and informing resource allocation strategies. Keywords: Physical education, family budget, cost reduction, importance, implications.